Comparative transcriptomics in adipose tissue of wild African elephants (Loxodonta africana) - Siew Shean Choong; Lisa Yon; Mongan, Nigel P.; Stansfield, Fiona J.; Allen, William R.; Fuentes-Utrillia, Pablo; Emes, Richard D. (2016)
Adipose tissue (AT) was reported to influence reproductive functions through regulation of the hypothalamus-pituitary-gonadal axis, and infertility in captive African elephants has been correlated to obesity. Next generation sequencing was utilised to generate transcriptomes of peri-renal AT from culled wild adults. RNA was extracted using Qiagen RNeasy Mini Kit, followed by quality evaluation with Agilent 2100 Bioanalyzer. RNA transcription was quantified using RNA-Seq (Illumina HiSeq). A total of 63,041,074 (F1), 83,963,786 (F2), and 56,783,624 (M1) paired reads were obtained. Differential gene expressions (DGE) were analysed using edgeR (www.bioconductor.org/packages/release/bioc/html/edgeR.html). Statistically significant DGE related to adipogenesis, lipogenesis and energy homeostasis were validated using qRT-PCR (ELOVL5, FASN, LEP, NR2F2, PPARγ, RXRα, SCD). DGE were also evaluated between sexes and ages (adult-juveniles) through qRT-PCR. Hierarchical clustering of gene expressions in adults revealed that genes expressed by the non-pregnant female (F2) was closer to those of the young growing bull, compared to the lactating female (F1). Furthermore, pregnant or lactating females showed a higher energy expenditure and lower lipogenesis level compared to young growing males. This may be due to high energy requirement for maintenance of pregnancy and lactation. However, energy homeostasis of the juveniles appeared to be more comparable between sexes, as mRNA expression failed to show a clear pattern of differential expression. This is indicative of similar growth rate in these juveniles. Results from this study provides baseline data on the dynamics of AT in wild African elephants. Ultimately, knowledge generated will be used to improve management and fertility of captive African elephants.